Influence of Sales Promotion, Hedonic Shopping Motivation and Fashion Involvement Toward Impulse Buying through a Positive Emotion. - Andani, Kiki; Wahyono, Wahyono (Universitas Negeri Semarang, 2018)
This study aims to determine the direct indirect influence of sales promotion, hedonic shopping motivation, fashion involvement and positive emotion as an intervening variable on impulse buying. The population of this research is customer of House of Smith Semarang. The number of samples is 100 respondents with incidental sampling technique through likert scale questionnaire. Data analysis using descriptive percentage and path analysis. The results show that sales promotion, hedonic shopping motivation, fashion involvement service affect impulse buying and positive emotion influence impulse buying and mediate the influence of sales promotion, hedonic shopping motivation, fashion involvement.